A Spectral Analysis of Near‐Surface Mean Wind Speed and Gusts Over the Iberian Peninsula. Issue 8 (25th April 2023) - Utrabo‐Carazo, Eduardo; Azorin‐Molina, Cesar; Aguilar, Enric; Brunet, Manola
Abstract: This study analyses for the first time observed surface mean wind speed (SWS) and gusts over the Iberian Peninsula (IP) in the frequency domain for 1961–2019, with the goal of exploring sources of predictability in the interannual and decadal scales. The main result is the high significant correlation between surface winds and the stratospheric polar vortex for periods close to 1 year with a time lag of about 2–3 months with respect to the antiphase, that is, a negative correlation in which the polar vortex modulates winds in the region. Furthermore, we found that the SWS and gusts are decoupled for periods between 9 and 11 years with a marked seasonal dependence in its intensity. Finally, we detected discrepancies between the spectra shown by surface winds from observations and ERA5‐Land reanalysis, suggesting that simulated data do not accurately reproduce the variability of surface wind speeds. Plain Language Summary: In the climate system, there are oscillations that are repeated with specific time periods over time; the best known example is the El Niño‐Southern Oscillation, which affects much of the world's climate. In this study, we apply a spectral analysis to: (a) characterize the spectrum of near‐surface mean wind speed and gusts in the Iberian Peninsula; (b) relate the oscillations of both wind variables with those of other parameters of the climate system; and, (c) identify sources of predictability. The most outstanding result is the high significant correlation between the mean wind speed and gusts with the stratospheric polar vortex with a time lag of about 2–3 months. This means that with an anomalously weak (strong) polar vortex we might expect strong (weak) surface winds 2–3 months later. This study has direct socioeconomic and environmental implications for for example, wind energy production, agriculture and hydrology, pollutant dispersion, among others, as it could predict interannual‐ to decadal‐scales wind speed behavior in the region. Key Points: Surface winds correlate with the stratospheric polar vortex in periods close to 1 year, with a 2–3 months lag with respect to the anti‐phase Surface mean wind speed and gusts are decoupled for periods between 9 and 11 years, being greater in summer and disappearing in winter Spectral analysis showed differences between observed and ERA5‐Land reanalysis surface winds